Ground Shock Attenuation on a Buried Cylindrical Structure by a Barrier - Sylwester Kobielak; Theodor Krauthammer; Adam Walczak (Shock and Vibration)
This paper presents results from studies on the influence of an attenuation barrier on soil stresses and pressures acting on a buried silo, caused by underground explosions at different distances from the structure. The attenuation barrier was made of PVC tubes that were placed between the explosive charges and the RC silo structure. Soil stress gages and pressure transducers were used to measure these data in the soil and on the structure, respectively. The influences of several parameters were analyzed for tests with and without an attenuation barrier between the silo and the explosive sources.